Sociology of education, its scientific profile and perspectives - Kota, Jaroslav (e-Pedagogium, 2019)
This article reflects the scientific profile of a borderline discipline conceived between sociology and pedagogy. It highlights the positivistic foundations of sociology and the normative science profile of education sciences. Attention is paid to the perspectives of research in the sociology of education, where the author distinguishes between macro-social research solving traditional issues of school, society and family, teachers and students, and relatively new specific topics which lack fully clarified research methodology.
Keywords: Key words: de-professionalisation of teachers; explanatory science; functionalist approach; normative science; pedagogy; positivism; professionalization of teachers; sociology; symbolic interactionism; conflict theory.